ВОКАЛЬНО-ХОРОВА ПІДГОТОВКА СТУДЕНТА ДО РОБОТИ З ХОРОМ В СИСТЕМІ КРЕДИТНО-МОДУЛЬНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2007)
In article questions of conditions of formation of the creative person of the singer, the conductor, the teacher of music are considered during singing-choral preparation on system of credit-modular training; a parity of the contents, the organization of vocational training to work from a mansion.